2010
DOI: 10.1007/s10067-010-1478-3
|View full text |Cite
|
Sign up to set email alerts
|

Very low levels of vitamin D in systemic sclerosis patients

Abstract: Vitamin D displays many extraosseous immunomodulatory effects. The aim of the study was to evaluate the level of vitamin D in patients with systemic sclerosis (SSc) and to analyze the associations between the concentration of the vitamin and clinical manifestations. In March-April 2009, 65 consecutive SSc patients underwent evaluation of vitamin D concentrations by the LIAISON immunoassay (normal 30-100 ng/ml). Serum levels between 10 and 30 ng/ml were classified as vitamin D insufficiency, while concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 21 publications
8
80
0
1
Order By: Relevance
“…Auto-antibodies profile, including anti-topoisomerase antibody I (Scl 70), anti-nuclear antibodies (ANA) and anti-centromere antibodies (ACA), has been reported to be associated with low hormone levels by Vacca et al, but following reports in the same findings failed [9][10][11]; [13][14][15][16][17]. Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Auto-antibodies profile, including anti-topoisomerase antibody I (Scl 70), anti-nuclear antibodies (ANA) and anti-centromere antibodies (ACA), has been reported to be associated with low hormone levels by Vacca et al, but following reports in the same findings failed [9][10][11]; [13][14][15][16][17]. Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18]. Acute-phase reactant including C-Reactive Protein (CRP) and Erythrocyte Sedimentation Rate (ESR) were extensively investigated in some studies reviewed [11][12][13][14]. Serum calcium, phosphate and bone turnover metabolism were mostly measured in those papers having BMD or parathyroid hormone (PTH) determination in their study protocol [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Low serum levels of 25-hydroxyvitamin D3 (25OH-D3) have been reported in patients with SSc. [3][4][5][6] The average concentration of 25OH-D3 was significantly lower in patients with a high degree of skin involvement (Rodnan skin score > 10) compared with patients with low degree of skin involvement (Rodnan skin score 10). 3 The effects of systemic vitamin D supplementation in SSc have been evaluated in some studies, however, the results vary between studies.…”
Section: Introductionmentioning
confidence: 99%